Guinea- Bissau : Technical Assistance Report-Enhancing Governance and the Anti-Corruption Framework: Next Steps. (IMF Staff Country Reports; Country Report, 2020)
Political instability has limited the development of Guinea-Bissau's institutional capacity. For example, tensions between the President and the leadership of the country's largest political party led to six changes of government between the 2014 and 2019 parliamentary elections. Previous IMF capacity development reports, ECF program reviews staff reports, and other diagnosis undertaken by the World Bank and the European Union have pointed to structural governance weaknesses and proposed corrective measures, in some cases, similar to those highlighted in this report. Regrettably, traction has been limited.